If a + b = 1 5 and a 2 b + a b 2 = 8 1 0 , what is a 3 + b 3 ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
( a + b ) 3 = a 3 + 3 a 2 b + 3 a b 2 + b 3 . But we know ( a + b ) 3 = 1 5 3 = 3 3 7 5 . And we know that 3 a 2 b + 3 a b 2 = 3 ( a 2 b + a b 2 ) = 3 ( 8 1 0 ) = 2 4 3 0 . Therefore, 3 3 7 5 = a 3 + b 3 + 2 4 3 0 , and a 3 + b 3 = 3 3 7 5 − 2 4 3 0 = 9 7 5 .
Did the Same way!!!!!
a^2b + ab^2 = 810 or, ab(a+b) = 810 or, ab*15=810 or, ab = 54 Now put the values in (a+b)^3 -3ab(a+b)
overrated!!!!!!
Log in to reply
I wasn't the one who chose the level. It was done automatically.
excellent answer
3375-2430=945 not 975
Did the Same Same Same Same Way!
Problem Loading...
Note Loading...
Set Loading...
a 3 + b 3 = ( a + b ) ( a 2 + b 2 − a b ) Here we know the value of a + b ,we just have to find the value of a 2 + b 2 , a b .First let,s find a b : a 2 b + a b 2 = a b ( a + b ) = a b × 1 5 = 8 1 0 → a b = 1 5 8 1 0 = 5 4 So a b = 5 4 .Now let,s find a 2 + b 2 : ( a + b ) 2 = 1 5 2 → a 2 + b 2 + 2 a b = 2 2 5 a 2 + b 2 + 2 ( 5 4 ) = 2 2 5 → a 2 + b 2 = 2 2 5 − 1 0 8 = 1 1 7 Now we have found the necessary data.Let,s calculate a 3 + b 3 : ( a + b ) ( a 2 + b 2 − a b ) → 1 5 × ( 1 1 7 − 5 4 ) = 1 5 × 6 3 = 9 4 5